Evaluation of Serum TNF-a in Patients with Oral Keratotic Lichen Planus and Comparing with Healthy Cases - Jafari SH; Khatibi M (Tehran University of Medical Sciences, 2000)
: Oral lichen planus (OLP) is a chronic and common disease of the oral mucosa, which its"netiology, phathogenesis and exact treatment is not definitely known. T-cell mediated immunity is the"nmost probable factor in pathogenesis of OLP. Since TNF-a primarily, as a cytokine, interfers T-Cell"nmediated immunopathologic reactions, it may also interfere with pathogenesis of OLP."nIn an observational case- control study, the values of TNF-a in serum of OLP patients were measured"nand compared with the values of healthy cases. 30 OLP patients and 30 healthy controls have examined"nwith ELISA technique. Data was obtained by observation questionnaire and examination."nThe mean value of TNF-a in case and control groups were 26.2 and 7.9 pg/ml, respectively, which"nshowed significant difference (PO.005)."nConsidering the TNF-a values with respect to sex and age did not show any significant difference,"nhowever the lower TNF-a value was obtained with increasing the age, and higher value observed in"nfemales. Higher values of TNF-a found in OLP patients compared with control group. It means TNF-a is"nan effective factor in OLP. Due to these findings new treatment protocols have been suggested.